Stress analysis of thin-walled laminated composite beams - Masturah Mohamad (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
An educational software for stress analysis of thin-walled I, T and C-sections has been developed which can aid students, lecturers and researchers in stress analysis of thin- walled open sections made of composite material. The software is based on the beam theory developed by Kollar and Springer which is limited for linear static analysis with linear stress-strain relationship. The software enables users to select type of load viz.: axial load, bending moment, torsional load and shear force. The ply stress and average stress of thin-walled open section will be instantly calculated by the software. The software also is able to calculate centroid location, shear center, equivalent axial stiffness, equivalent bending stiffness, rate of twist and torsional stiffness of the beam. Results obtained from the present software were validated against the FEA results using ANSYS and they were found to be in good agreement. Results are presented in tabular and graphical form for various different symmetrical and unsymmetrical thin walled sections with different layup for web and flanges. Parametric study can also be carried out with the aid of the software which can be useful in the design of thin-walled section made of composite material. The software is intended to be used as a resourceful tool for effective teaching and learning process on thin-walled structures related courses.